Stock overreaction behaviour in Bursa Malaysia: does the length of the formation period matter? - Ali, Norli; Md Nassir, Annuar; Hassan, Taufiq; Zainal Abidin, Sazali (British Academic Journals, 2011)
This paper investigates whether stock overreaction behaviour in Malaysian stock market is sensitive to the length of the formation period. Using the basic framework of De Bondt and Thaler (1985), this study find that stock overreaction behaviour in this market is sensitive to the length of the formation period. Significant evidence of stock overreaction effect is documented in the longer formation period of up to 5-year, while for the medium formation period of 2-year, there is no clear evidence of stock overreaction behaviour. Evidence of stock overreaction behaviour is also reported for the shorter-term of 1-year, however, it may not be economically profitable after taken into account the transaction cost. This study also shows that size cannot explain the documented overreaction effect. However, the results suggest that the overreaction effect subsided after adjustment to time-varying risk.